Ekstrakurikuler Wawasan Kebangsaan sebagai Media Penguatan Minat dan Pendidikan Pancasila di Tingkat Sekolah Menengah Atas - Ridha, Muhammad Kamil; Kiptiah, Mariatul (PAKAR Pendidikan, 2025)
This research is important to see the existence of extracurricular national insight in order to strengthen students' interests, its existence in integrating the content of Pancasila learning into extracurricular activities that make this extracurricular interesting, and this extracurricular is a pilot project that does not yet exist in other schools. This research uses qualitative research methods, with data collection techniques of observation, interviews, and documentation. The subjects of this research are the principal, extracurricular coaches, and students who are members of extracurricular activities from grade 10 to grade 12. Data analysis techniques with data selection, data presentation and conclusion drawing and by testing data validity through triangulation. The results showed: that interest strengthening was carried out not only relying on internal interests but also stimulating interests that arose due to stimuli from the environment, interests channeled through extracurricular activities were measured to determine the extent to which extracurricular activities could accommodate the interests of students properly seen from the increase in knowledge and abilities of students, and the climate made supportive so that students could channel their interests optimally by presenting a recreative climate without discrimination by optimizing the role of teachers. In conclusion, the presence of this extracurricular activity is able to accommodate the interests of students well, able to integrate with the content of Pancasila Education and optimal support from the school.